Death anxiety of doctors and nurses with levels of depression related to death and the factors affecting them (Annals of Medical Research, 2021)
Aim: This study was carried out to determine the factors affecting the anxiety levels of death and death related depression of doctors and nurses working at a Hospital.Materials and Methods: The population of the this study, which was planned as cross-sectional, consists of all the doctors and nurses working at a State Hospital (n=288), while the sample consisted of 280 medical personnel. Data was collected using a 17 item Patient Identification Form including socio demographic and , including individual characteristics which were thought to be related to death anxiety of doctors and nurses, and Death Anxiety Scale (DAS), and Death Depression Scale(DDS).Results: The mean score of Death Depression Scale for women is higher than men and the mean score of death depression scale for nurses is significantly higher than doctors (p=0.0001). There is no significant difference between the scores of DDS in terms of the marital status of medical personnel, having children or not, loving the work or not, the department they work, being exposed to serious danger of death, the situation of desensitization and feelings and thoughts about the death exposed to (p>0.05). The mean scores of women’s Death Anxiety Scale are significantly lower than men (p=0.009), scores of single people (p=0.009) are lower than married ones, scores of people who don’t have any children are lower than the people who have children (p=0.012).Conclusion: In this study, the most important determinant of death anxiety and depression related to death was determined as female, nurse, and not having any children and work in surgical unit.